1998
DOI: 10.1103/physreve.57.4250
|View full text |Cite
|
Sign up to set email alerts
|

Model for convection in binary liquids

Abstract: A minimal, analytically manageable Galerkin type model for convection in binary mixtures subject to realistic boundary conditions is presented. The model elucidates and reproduces the typical bifurcation topology of extended stationary and oscillatory convective states seen for negative Soret coupling: backwards stationary and Hopf bifurcations, saddle node bifurcations to stable strongly nonlinear stationary and traveling wave (TW) states, and merging of the TW solution branch with stationary states. Also uns… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…From a comparison between the experimental data and the theory in Ref. [1], it has been found that the separation ratio in the fluid investigated here takes a high value of c ¼ 1850: This opens for the future the possibility to perform an experimental proof of the square roll flow pattern which has been predicted in Ref. [1].…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…From a comparison between the experimental data and the theory in Ref. [1], it has been found that the separation ratio in the fluid investigated here takes a high value of c ¼ 1850: This opens for the future the possibility to perform an experimental proof of the square roll flow pattern which has been predicted in Ref. [1].…”
Section: Discussionmentioning
confidence: 76%
“…Again it is clearly observed that a strong convective flow appears below DT Ã 0 : The solid line is a fit of the theoretical dependence of the amplitude on as is given in Ref. [1]. The free fit parameter is the separation ratio c which is determined from the fit to be c ¼ 1850 AE 100: It should be noted that long-term measurements have shown that the convective flow is stable over time and that no oscillations of the convection amplitude can be observed.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…This extended model incorporates the Soret and Dufour effects. However, the Dufour effect is exceedingly weak in liquids and can be safely neglected [9], while the Soret effect can be significant and will be taken into account hereafter. Therefore, in what follows the heat J h and mass J m fluxes are given by…”
Section: Mathematical Modelmentioning
confidence: 99%